Alienation versus acceptance. Looking at immigrant communities in the French cinéma de banlieue from 1995 to 2019 - Majewicz, Natalia (Studia Etnologiczne i Antropologiczne, 2023)
Searching one’s own identity in a foreign culture is one of the indispensable elements of the modern world. The purpose of this paper is to characterize the way in which cinéma de banlieue portrays dominant problems faced by immigrants in everyday life in France. Methodologically, the article is based on the research tools proposed by Manon Grodner and centers around three domains of public discourse, such as democracy, society and laicity. In particular, the focus is on the antagonistic picture of men and women. The research covers the period from 1995, the official date of the beginning of this cinematic movement, to 2019, the year of the release of the film Banlieusards.